EXPLORING THE POTENTIAL OF EUDRAGIT FOR DEVELOPMENT OF MICROPARTICLES OF WATER SOLUBLE DRUG USING QUALITY BY DESIGN APPROACH - SHARMA, SHAILESH; SETH, NIMRATA (International Journal of Applied Pharmaceutics, 2019)
Objective: In the present protocol, employability of polymethacrylate polymer Eudragit RS100 for development of microparticles of water soluble drug with desired values of response variables was investigated by central composite optimization design through application of Design Expert® software (Series DX10). Methods: The microparticles were developed by emulsion solvent evaporation process employing Eudragit RS100. Two effective independent variables drug: polymer ratio and stirring speed were selected to assess performance prospective of Eudragit on mean particle size, entrapment efficiency, percent yield and drug release in 12 h of microparticles. Thirteen batches generated by software were prepared and subjected to different characterization test parameters obligatory for the evaluation of formulation. Validation of optimization model and Statistical interpretation of results was done using Analysis of Variance (ANOVA) Results: ANOVA indicated that the independent variables had significant effect on response variables. Optimized formulation demonstrated close agreement amongst experimental and predicted responses with high desirability factor. In vitro drug liberation study for optimized formulation proposed a sustained release of drug from microparticles. Conclusion: In conclusion, optimization technique was imperative in indicating the efficient applicability of Eudragit RS100 polymer in controlling the drug release of hydrophilic drugs.